Progressive Respiratory Insufficiency in a Teenager with Diaphragmatic Hypomotility Due to a Novel Combination of Gliomedin Gene Variants - Benjamin Eurich; Catharina Nitsche; Margot Lau; Britta Hanker; Juliane Spiegler; Guido Stichtenoth (MDPI AG, 2022)
Lethal congenital contracture syndrome 11 (LCCS11) is a form of arthrogryposis multiplex congenita (AMC) which is associated with mutations in the gliomedin gene (GLDN) and has been known to be severely life-shortening, mainly due to respiratory insufficiency. Patients with this condition have been predominantly treated by pediatricians as they usually do not survive beyond childhood. In this case report, we present a young adult who developed severe progressive respiratory insufficiency as a teenager due to diaphragmatic hypomotility and was diagnosed with LCCS11 following the discovery of compound heterozygous pathogenic variants in GLDN. This case demonstrates the importance of screening for neuromuscular diseases in well-child visits and follow-ups of patients at risk for gross and fine motor function developmental delay. It also underscores the significance of including LCCS11 and other axonopathies in the differential diagnosis of juvenile onset of respiratory insufficiency, highlights that patients with this condition may present to adult practitioners and questions whether the nomenclature of this condition with various phenotypes should be reconsidered due to the stigmatizing term 'lethal'.